Pengaruh Sarcotesta dan Pengeringan Benih serta Perlakuan Pendahuluan terhadap Viabilitas dan Dormansi Benih Pepaya (Carica papaya L.) - Maryati Sari; Endang Murniati; M. Rahmad Suhartanto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
Improved seed longevity by seed drying and application of  phenolic compound as natural antioxidant is the topic of this research. In many cases the sensitivity of papaya seed to drying is being the limit factor because of desiccation injury or induced dormancy. There is phenolic compound on the sarcotesta surrounding papaya seed which may act either as antioxidant or as germination inhibitor. The effect of sarcotesta and seed drying on viabillity and dormancy was studied. The experiment was conducted in July - October 2004, located at Bogor Agricultural University, used papaya seed (IPB-1) which harvested from Pusat Kajian Buah Tropika (PKBT) farm in Bogor. In the last study, seed was dried in the absence and presence of sarcotesta until 11-12% and 6-7% moisture content (mc). After drying, seed viability was measured by tetrazolium test.  The hardness of seed was also measured using penetrometer.  Seed germination was tested by (1) soaking on 10% KNO3, (2) scarification on water using  electrical stirrer, (3) soaking on 10% KNO3  with scarification using electrical stirrer, (4) scarification on the  hot water (50oC) followed by soaking on 10% KNO3.   In the absence of sarcotesta, the viability of 6-7% mc seed was as high as 11-12% mc seed. There was neither viability reduction nor induced dormancy. Whereas in the presence of sarcotesta, there was also no viability reduction but the dormancy was induced. The dormancy of seed with 11-12% mc was longer than seed with 6-7% mc. Scanning electron microscopy images showed that sarcotesta was removed by cleaning treatment before drying. On the contrary, sarcotesta was not completely removed from the seed and became more impermeable when cleaning was done after drying.This research can not suggest the most effective  pre-treatment to break the dormancy. The mechanism of the dormancy is discused.   Key words: Carica papaya L., seed drying, sarcotesta, seed viability, seed dormancy